2016
DOI: 10.18702/acf.2016.12.2.2.102
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of recycled nylon fibers as reinforcing material in mortar

Abstract: Disposing of waste fishing nets has been a major issue in the sea environment. Although the storage of such nets has not caused a serious safety hazard to date, it is important to find suitable recycling solutions. In this study, the authors investigate the utilization of recycled waste fishing nets in fiber-reinforced mortar and compare the mechanical properties of such mortar made with recycled waste fishing nets to those of mortar made with PVA (polyvinyl alcohol) short fibers. Two types of recycled nylon f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Fortunately, these waste materials can be recycled and used as concrete fibers. Examples of these recycled fibers are nylon fibers recycled from fishing nets [21][22][23], recycled brass fiber [24], carbon fibers [25,26] textile, acrylic, and waste glass fibers [27], etc. Previous works showed that the recycled fibers are also effective in a similar way of the new fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, these waste materials can be recycled and used as concrete fibers. Examples of these recycled fibers are nylon fibers recycled from fishing nets [21][22][23], recycled brass fiber [24], carbon fibers [25,26] textile, acrylic, and waste glass fibers [27], etc. Previous works showed that the recycled fibers are also effective in a similar way of the new fibers.…”
Section: Introductionmentioning
confidence: 99%